Characterization of a silica-aerosol in a sintering process by wide-angle light scattering and principal component analysis - Huber, Franz; Will, Stefan (Journal of Aerosol Science, 2018)
In nanoparticle synthesis, a large variety of sizes and morphologies can be observed depending on the process parameters. Besides fractal-like aggregates built from primary particles and non-aggregated spherical particles also mixtures of particle fractions are obtained. For industrial process control, real-time capable algorithms for multi-variate parameter determination are required. In this work, principal component analysis is employed for inverting scattering data from elastic light scattering measurements to obtain information about the size distribution of particle fractions like fractals and spheres and the mixing ratio. Additionally in the case of fractals their fractal dimension is determined. The method is employed on simulated data and experimental data from wide-angle light scattering (WALS) measurements on a silica aerosol synthesized in a chemical vapor synthesis process with a proceeding sintering step of variable degree.
Keywords: Elastic light scattering; Nanoparticles; Principal component analysis; Fractal aggregates; Mie scattering; Sintering; Size distribution